The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1108/20436231111167219
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts in family firms: state of the art and perspectives for future research

Abstract: Purpose -The aim of the paper is to provide a systematic overview of the literature dealing with business-related conflicts between family members in (their) family firms (FF). On the basis of this focus, the research questions are: Which delimitable topics with regard to contents can be identified in the literature on conflicts in FF? Which findings are available referring to this and how were they generated? Which options can be derived for future research? Design/methodology/approach -The analysis is based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 36 publications
(51 reference statements)
1
64
0
3
Order By: Relevance
“…Another stream of research has focused on disentangling the effects of different types of conflict (e.g., Eddleston, Otondo, & Kellermanns, 2008;Danes et al, 2000). Research has confirmed the harmful effect of relational conflict on family firm performance Frank et al, 2011;Nos e, Korunka, Frank, & Danes, 2017). Some factors, like altruism between family members and family cohesion and adaptability (Nos e et al, 2017), have shown a moderating effect in these relationships.…”
Section: Conflict Management In Family Firmsmentioning
confidence: 91%
See 2 more Smart Citations
“…Another stream of research has focused on disentangling the effects of different types of conflict (e.g., Eddleston, Otondo, & Kellermanns, 2008;Danes et al, 2000). Research has confirmed the harmful effect of relational conflict on family firm performance Frank et al, 2011;Nos e, Korunka, Frank, & Danes, 2017). Some factors, like altruism between family members and family cohesion and adaptability (Nos e et al, 2017), have shown a moderating effect in these relationships.…”
Section: Conflict Management In Family Firmsmentioning
confidence: 91%
“…Although the topic of conflict in family firms has captured the attention of academics from a variety of backgrounds (Smyrnios, Poutziouris, & Goel, 2013), the study of conflict management in family firms is still in an early stage of development (Debicki, Matherne, Kellermanns, & Chrisman, 2009;Frank et al, 2011;Sharma, De Massis, & Gagne, 2014). The theoretical frameworks used are sparse (Frank et al, 2011), and relevant knowledge of the conflict management field has yet to be integrated into the family business field (Caputo et al, 2018).…”
Section: Conflict In a Unique Setting: The Family Firmmentioning
confidence: 99%
See 1 more Smart Citation
“…Entre os tópicos estudados, destacam-se: sucessão (Brockhaus, 2004), famí-lia (Dyer, 2003;Dyer & Dyer, 2009), estratégia (Sharma, Chrisman, & Chua, 1997;Chrisman, Chua, & Sharma, 2005;Astrachan, 2010), administração financeira e desempenho (Mazzi, 2011), governança (Aguilera & Crespi-Cladera, 2012), cultura (Fletcher, Melin, & Gimeno, 2012), conflito (Frank, Kessler, Nosé, & Suchy, 2011), gênero (Jimenez, 2009), valor socioemocional (Berrone, Cruz, & Gomez-Mejia, 2012), familiness (Frank, Lueger, Nosé, & Suchy, 2010) e inovação (De Massis, Frattini, & Lichtenthaler, 2012). Contudo, não foram realizados ainda estudos sistemáticos de revisão da literatura sobre empreendedorismo em empresas familiares.…”
Section: Introductionunclassified
“…Conflict resolution plays a major part in the family business literature (see Levison, 1971;Harvey and Evans, 1994;Sorenson, 1999;Davis and Harveston, 1999Eddleston, Otondo and Kellermanns, 2008;and Frank, Kessler, Nose and Suchy, 2011 (Smith, 2006: 57).…”
Section: Authoring Second-generation Entrepreneur Storiesmentioning
confidence: 99%